Dilema Upaya Hukum Terhadap Penyadapan - Yuvens, Damian Agata; Widigda, Rangga Sujud; Sharifa, Aisyah (Jurnal Hukum & Pembangunan, 2017)
Although interception is not a new institution in Indonesia, unfortunately the regulations are still scattered and different from one to another. In its context as authority of law enforcer, interception does not have horizontal balancing mechanism. Referring to considerations of Constitutional Court of the Republic of Indonesia in expanding the scope of pre-trial, apparently those considerations could be applied towards interception, thus conceptually, it can be said that pre-trial could be stretched to include interception. Nevertheless, there is incompatibility between concept of pre-trial and regulations concerning interception in the prevailing laws